Building Sense of Community at a Distance - Alfred P. Rovai (International Review of Research in Open and Distributed Learning, 2002)
This article challenges the belief that strong sense of community is limited to the traditional classroom and proposes that the virtual classroom has the potential of building and sustaining sense of community at levels that are comparable to the traditional classroom. Drawing on research literature, the concept of learning community is applied to the virtual classroom by taking on the issue of how best to design and conduct an online course that fosters community among learners who are physically separated from each other. Course design principles are described that facilitate dialogue and decrease psychological distance, thereby increasing a sense of community among learners.